Marchesini, R. (2021). The Virus Paradigm. A Planetary Ecology of the Mind (S. De Sanctis, Trans.) - a Marca, Pablo (Journal of Ecohumanism, 2022)
Marchesini, R. (2021). The Virus Paradigm. A Planetary Ecology of the Mind (S. De Sanctis, Trans.)